Tourism Expectation as Moderator of Promotion Objectives and Promotion Mix on Tourist Interest - Rahayu, Denok Wahyudi Setyo; Septiawan, Bambang; Hamidah, Aqnes Dwi Sakti; Terizla, Rizky Fredrin (Aptisi Transactions On Technopreneurship (ATT), 2026)
Promotion objectives, tourism promotion mix, and expectations play significant roles in attracting tourists to destinations. Videos have emerged as effective promotional tools, showcasing the actual conditions of tourist attractions. This research investigates how promotional objectives and the tourism promotion mix, with the moderation of expectations, can influence tourist interest. A total of 247 respondents were sampled for this study. The respondents evaluated videos of Kebon Rojo Park, Blitar, East Java, and completed a questionnaire. The analysis method used was Partial Least Squares (PLS), suitable for handling complex data with multiple variables. The study found that both promotion objectives and the tourism promotion mix positively influenced tourist interest. However, expectations did not moderate the relationship between the promotional strategies and tourist interest. This indicates that expectations do not strengthen or weaken the effects of promotional objectives and tourism promotion mix on tourist interest. The research suggests that while expectations play a role in shaping perceptions, the key to attracting tourists lies in effective promotional strategies tailored to the target market segment. This highlights the importance of using accurate and attractive promotional materials to stimulate interest in visiting destinations like Kebon Rojo Park.